Location model of the timber industry and its environmental impact. Pucallpa-Ucayali Region - Meza Arquiñigo, Carlos (2015)
The study of “Model location of the timber industry and its environmental impact. Pucallpa - Ucayali region”. The purpose was the formulation of a model medereras location of industries and the impact on the environment in order to contribute to an appropriate urban planning. For this purpose were located and wood industries were georeferenced in the city of Pucallpa through thematic maps, building and adding to the base of graphic data and attribute information with correspondiete industrial logging companies. Then the mapping model is structured as logical sequences for the production of thematic maps that will serve for spatial analysis and monitoring of environmental impacts on air, water, soil, living organisms, especially human beings is shown.